STRATEGI BERTAHAN PEDAGANG STREET FOOD PADA MASA PANDEMI COVID-19 DI KAWASAN WISATA ULEE LHEUE KOTA BANDA ACEH - Noratul Ikramah (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2023)
The impact of the Covid-19 pandemic has weakened the existence of street food traders in the Ulee Lheue tourist area to maintain strategies to be able to survive the Covid-19 pandemic in order to continue running their businesses so they can meet their economic needs. This research explains the forms of survival strategies and the challenges faced by street food traders in maintaining their business during the Covid-19 pandemic. The research method used is qualitative research using a case study approach. Data collection techniques carried out by in-depth interviews, observation and documentation. The results of this study explain that street food traders' strategies to maintain their business during a pandemic start by using active strategies, passive strategies, and network strategies. As well as the challenges of street food traders in dealing with the Covid-19 pandemic are as follows: Decreased income, limited capital, human resources (knowledge, skills and insights), lack of availability of raw materials, closed locations and empty of visitors.